Penerapan Sanksi Tambahan terhadap Pengguna Knalpot Non-Standar dalam Undang-Undang Lalu Lintas - Abdul Majid, Luky; Guntara, Deny; Abas, Muhamad (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2023)
This study analyzes the implementation of additional sanctions for users of non-standard mufflers in accordance with Law Number 22 of 2009 concerning Traffic and Road Transportation. The use of noisy racing mufflers is considered a criminal offense, but the existing sanctions are deemed ineffective. The research adopts a normative juridical approach with a legislative perspective. The findings reveal that additional sanctions that can be imposed on users of noisy mufflers include bringing the muffler closer to the user's ears or engaging in specific sports activities. Factors influencing the effectiveness of law enforcement encompass regulations, law enforcement agencies, infrastructure, society, and culture.